A configuração do espaço: uma abordagem de romances Queirosianos - Oliveira, Raquel Trentin (2008)
This work presents, as its central concern, a study of the configuration of the narrative space in the novels O Crime do padre Amaro (1875), O Primo Basílio (1878) e Os Maias (1888), by Eça de Queirós. The development of the analysis sheds light upon the fictional form held by the space in the literary text, the perception of space and the ways it operates on the structure and on the semantics of the narrative. These are the major issues which constitute the content of each of the three chapters of this thesis. The analysis made tries to demonstrate that the space acquires a distinguishing nature through the combination and selection processes in which it participates and, primarily, due to the fact that it constitutes the field of experience for fictional subjects. This analysis also stresses the close link between the configuration of the novel s space and the characters perception; moreover, it shows that the space may develop different roles in the narrative since it provides support to the narrative conflict, to characterization, as well as it expands the meanings of the text.